YO‐IFOS Guidelines for Pediatric ENT Surgery during COVID‐19: An Overview of Recommendations. (25th December 2020) - Din, Taseer; Abdalla, Tagwa; Chiesa‐Estomba, Carlos; Simon, François; Teissier, Natacha; Thomas, Izaskun; Fagan, Johannes; Peer, Shazia
Abstract : Objective/Hypothesis: To review the literature on pediatric ENT COVID‐19 guidelines worldwide, in particular, surgical practice during the pandemic, and to establish a comprehensive set of recommendations. Study Design: Review. Methods: A comprehensive literature review through an independent electronic search of the COVID‐19 pandemic in PubMed, Medline, Google, and Google Scholar was performed on April 26–30, 2020. Resources identified comprised of published papers, national and international pediatric ENT society guidelines. Results: Fourteen guidelines fit the inclusion criteria. Key statements were formulated and graded: 1) Strong recommendation (reported by 9 or more/14); 2) Fair recommendation (7–8/14); 3) Weak recommendation (5–6/14); and 4) Expert opinion (2–4/14). Any single source suggestion was included as a comment. Highly scored recommendations included definition of urgent/emergent cases that required surgery; surgery for acute airway obstruction; prompt diagnosis of suspected cancer; and surgical intervention for sepsis following initial first‐line medical management. Other well scored recommendations included senior faculty to perform the surgery; the use of open approaches rather than endoscopic ones; and avoidance of powered instruments that would aerosolize virus‐loaded tissue. A tracheostomy should be performed on a case by case basis where key technical modifications become necessary. Conclusions: The COVID‐19 pandemic will have a profound short and long‐term impact on pediatric ENT practice. During this rapidly evolving climate, guidelines have been based on local practice and expert opinion. Until evidence‐based practice in the COVID era is established, a comprehensive set of recommendations for pediatric ENT surgical practice based on a review of currently available literature and guidelines, is therefore, appropriate. Laryngoscope, 131:1876–1883, 2021